Evaluation of Wound Healing Activity of Stem Bark of Albizzia lebbeck - Upadhyay, Rajesh Kumar (International Journal of Pharmaceutical & Biological Archive, 2014)
Evaluation of Wound Healing Activity of Stem Bark of Albizzia lebbeck